Comparison of knowledge, attitude and practice of diabetic patients taking treatment at private and public health centre in an urban area - Kumar, Purushottam; Ankushe, Rajendra T.; Doibale, Mohan K.; Kuril, Bina M.; Andurkar, Smita P.; Srivastava, Abhay (International Journal Of Community Medicine And Public Health, 2018)
Background: Diabetes is undoubtedly one of the most challenging health problems of the 21st century. Diabetes and its complications are major causes of early death in most countries. According to IDF approximately 5.1 million people aged between 20 and 79 years died from diabetes in 2013, accounting for 8.4% of global all-cause mortality among people in this age group. With 1.2 million deaths in 2013, this region [SEA] has the second highest number of deaths attributable to diabetes of any of the seven IDF regions. That figure represents 14.2% of all adult deaths in the Region. India is the largest contributor to regional mortality, with 1.1 million deaths attributable to diabetes in 2013. Methods: The study was a cross sectional study to compare the knowledge, attitude and practice of diabetic patients taking treatment at private and public health centre in an urban area. This study was conducted in a city of field practice area of our medical college, during the period of July 2016 to October 2016. We purposively selected 50 diabetic patients from public health centre and 50 diabetic patients from Private health centre. Diabetic patients were interviewed based on our predesigned pretested questionnaire. Results: 54% diabetic patients taking treatment at private health centre had average to good knowledge as compared to 28% at public health centre. 34% diabetic patients taking treatment at private health centre had positive attitude as compared to 6% at public health centre. 20% diabetic patients taking treatment at private health centre had average to good practice as compared to 6% at public health centre. Conclusions: Knowledge, attitude and practice of diabetic patients taking treatment at private health centre were better than taking treatment at public health centre.